Peningkatan Pengetahuan Pola Makan Sehat melalui Flash Card - Zubaedah Zubaedah; Dwi Puji Lestari (Universitas Al-Hikmah Indonesia, 2017)
The purpose of this research was to determinate the proccess of implementation flasch card to increase knowledge of healty dietary habit in Group B Al Hub Kebayoran Baru South of Jakarta. This research is an action research which refers to the model of a classroom Action Research Kemmis and Mc. Taggart. The subject of this research are children in Group B Al Hub Kebayoran Baru South of Jakarta there are 10 children. The steps of this research : (1) Planing (2) Action (3) Observation (4) Reflection. Data analysis used quantitative and qualitative. Data analysis qualitative used Miles and Hubberman model. This research do in two cycles, there are cycle I and II. The end result of the overall analysis of the data is the percentage in 91,17% cycles II which showed from precycle is 29,37 % up to cycles I 61,94%.